2007
DOI: 10.1007/bf03405415
|View full text |Cite
|
Sign up to set email alerts
|

Solidarity or Financial Sustainability

Abstract: Objectives: Although community-based health insurance (CBHI) seemed promising to improve access to health care, its implementation has been slow and laborious. We hypothesize that the existing tension between the competing objectives of solidarity and financial sustainability that are pursued by CBHI may partly account for this. This paper aims to evaluate if there is a gap between CBHI subscribers' values and their promoters', and to determine which characteristics of subscribers and CBHIs are associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The large majority of papers were based on cross-sectional and/or household surveys, case studies and interviews. Two studies [ 12 , 13 ] were carried out from a provider perspective and highlighted problems with poor understanding of schemes by ministry staff and conflicts between subscriber and promoter values. Several studies focused on willingness to pay [ 14 - 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The large majority of papers were based on cross-sectional and/or household surveys, case studies and interviews. Two studies [ 12 , 13 ] were carried out from a provider perspective and highlighted problems with poor understanding of schemes by ministry staff and conflicts between subscriber and promoter values. Several studies focused on willingness to pay [ 14 - 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study, conducted in Senegal, it was found that implementation of CHI schemes has been slow and laborious. This was explained in part by tension between the competing objectives pursued by both promoters and subscribers [ 7 ]. In addition to minimal knowledge and understanding of CHI by providers and policy implementers, studies have indicated that poor knowledge and understanding on the part of the schemes beneficiaries is also a contributing factor to low enrollment in Uganda [ 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only two key studies in Africa have focused on knowledge and understanding of CHI by managers of health services. A study on the Maliando scheme in Guinea Conakry offered insight into perceptions of health providers at both operational and managerial levels [ 6 ], while another study looked at solidarity and financial sustainability based on an analysis of the values of CHI subscribers and promoters in Senegal [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental rule in programme evaluation is that “impact questions should ask whether a program achieved its ultimate objectives” [ 5 ]. A pre-payment scheme does aim to increase utilisation and, ultimately, help restore the health of its users.…”
Section: Methodological Issues In Evaluating Pre-payment Schemesmentioning
confidence: 99%
“…In Rwanda, funding agencies sponsor free CBHI coverage for the worst-off, but research results are not yet available. In fact, it is well known that CBHI [ 4 , 5 ] and cost-recovery schemes based on user fees [ 6 ] are not concerned with the worst-off nor with equity.…”
Section: What the New Study Addsmentioning
confidence: 99%